Achieving sustainable goals in agroecosystems through the optimization of agricultural resources integrating the water-nitrogen-carbon nexus - Mo Li; Pingan Zhang; Aizheng Yang; Xiaofang Wang; Yan Sha; Qiang Fu (iScience)
Summary: This study investigates the synergistic utilization of straw, water, and nitrogen resources in agricultural ecosystems to optimize sustainable management practices. Focusing on a tomato-corn-soybean agroecosystem, the research quantifies the interactions within the water-nitrogen-carbon nexus and evaluates various straw utilization strategies. Results show that, under optimized water (196-157-123 mm) and nitrogen (207-236-84 kg/ha) conditions, the water and carbon footprints decreased by 2.25–5.46% and 3.37–13.82%, respectively, compared to local practices. Economic benefits and overall quality improved by 8.27–21.06% and 4.06–7.63%, respectively. Prioritizing straw return to the field and straw biochar preparation scenarios enhanced system coordination by 1.41–9.62%. These findings offer valuable insights for decision-makers, providing strategies for sustainable agriculture that balance resource optimization, food security, and environmental protection.